RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND SLEEP QUALITY IN ADOLESCENTS - Aliah, Aliah; Bachtiar, Farahdina; Agustiyawan, Agustiyawan; Sirada, Andy (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2023)
Background: One of the health problems in adolescents is lack of sleep. In previous studies revealed that physical activity is one of the factors that affect the quality of a person’s sleep. Method: This research is a correlational quantitative research with a cross sectional approach. The sample in this research was Senior High School X Jakarta students. The parameters used in this study were the PSQI to assess sleep quality and the IPAQ-SF to assess physical activity level. Results: The results of data processing with SPSS 25.0 found that as many as 104 (66,2%) of the 157 respondents who were had poor sleep quality. The results of the correlation test using the Spearman Test between physical activity and sleep quality obtained a significance value of 0,001 and a correlation coefficient (r)= 0,252. Conclusion: In summary, there is a significant relationship between physical activity and sleep quality in adolescents with very weak relationship. There is a unidirectional relationship indicating that the higher the physical activity, the better the quality of sleep. Recommendation: Further studies are required by taking into account other risk factors that have a significant impact on sleep quality.